Lemahnya Pengungkapan Emisi Karbon di Indonesia: Analisis Dominasi Ukuran Perusahaan atas Profitabilitas dalam Menentukan Nilai Perusahaan - Siti Nurlatifah (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2026)
This study empirically evaluates the influence of carbon emission disclosure, firm size, and profitability on firm value within the cyclicals subsector of manufacturing companies listed on the Indonesia Stock Exchange during the 2020–2024 period. Utilizing a quantitative approach and purposive sampling technique, a total of 23 companies were selected as the sample. The analytical methods include descriptive statistics, classical assumption tests (normality, multicollinearity, autocorrelation, and heteroscedasticity), and multiple linear regression, processed using SPSS version 27. The findings reveal that carbon emission disclosure (CED) and profitability (Return on Assets/ROA) have no significant impact on firm value as measured by Tobin’s Q. Conversely, firm size demonstrates a positive and significant influence on firm value, indicating that scale is a strategic determinant in shaping investor perceptions and market valuation. The implications suggest that operational aspects play a more dominant role in influencing firm value than short-term profitability or sustainability disclosures. These results contribute to the growing body of literature examining the relationship between ESG indicators and market performance in emerging economies, and they highlight the need for more integrated valuation models that reflect both financial and non-financial dimensions of corporate strategy.